BMP and NODAL paracrine signalling regulate the totipotent-like cell state in embryonic stem cells - Jagdish, Sanidhya; Joumier, Loick; Dhakal, Sabin; Duran-Bishop, Gilberto; Usama, Mohammed; Malleshaiah, Mohan (Frontiers in Cell and Developmental Biology, 2026)
Cell–cell communication coordinates signalling between cells to guide context-dependent cell fate decisions such as proliferation, differentiation, and lineage specification. Such communication mechanisms are poorly understood in regulating the stem cell states. In this study, we investigate how cell-cell communication regulates cell fate transitions in heterogeneous embryonic stem cell populations, with a particular focus on totipotent-like cells that resemble the two-cell stage embryo. Using single-cell RNA sequencing in combination with computational frameworks, we map ligand–receptor interactions and model downstream regulatory effects across various stem cell states. We functionally validate the predictions by selectively perturbing signalling pathways under specific culture conditions. Our data reveal the key roles of BMP and NODAL (TGF-β) signalling in mediating intercellular communication to shape stem cell identity and heterogeneity. These findings enhance our understanding of the signalling logic that governs early developmental cell fate decisions, providing new insights into stem cell biology with broad implications for regenerative medicine and developmental modelling.